Dielectric and biodegradation properties of biodegradable nano-hydroxyapatite/starch bone scaffold - Beh, Chong Youa; Cheng, Ee Meng; Mohd Nasir, Nashrul Fazli; Mohd Tarmizi, Emma Ziezie; Khor, Shing Fhan; Eng, Swee Kheng; Abdul Majid, Mohd Shukry; Mohd Jamir, Mohd Ridzuan (Elsevier, 2022)
This study is aim to investigate the dielectric properties (dielectric constant, ε′ and loss factor, ε′′) and the biodegradation properties of the nano-hydroxyapatite/starch bone scaffold with various starch proportion in simulated body fluid. The nano-hydroxyapatite/starch bone scaffolds with starch proportions 30, 40, 50, 60, 70, 80, and 90 wt.% were fabricated. The ε′ and ε′′ of nano-hydroxyapatite/starch composite decrease when frequency increases. However, it increases when starch proportion and temperature increase. The biodegradation properties of the nano-hydroxyapatite/starch bone scaffold can be improved when the dielectric properties and porosity are enhanced. The enhancement of dielectric properties and porosity is due to the increment of starch proportion. The nano-hydroxyapatite/starch bone scaffold with the high starch proportion exhibits nano-hydroxyapatite/starch interfaces with strong intermolecular interactions that can stabilize biodegradation and biomineralization. The dielectric properties of the simulated body solutions are highly sensitive to the variation of the ion concentrations (calcium and phosphate). The nano-hydroxyapatite/starch bone scaffold with 80 wt.% starch proportion exhibits significant dielectric and biodegradation properties. It has potential to be a biodegradable inorganic/organic bone scaffold.